Martadinata Village Green Farming through the Community Empowerment based Marta Tani Mandiri Program - Choirul Dwi Cahyo; Yedo Kurniawan; Adhelia Hasri Miracahyani (Prospect Publishing, 2025)
Sustainable community development is a goal of a country and companies can realize this goal. As stakeholders in the community, companies can implement Social and Environmental Responsibility (TJSL) in communities that intersect with the operational area. Community empowerment programs aim to create positive contributions to economic improvement, environmental preservation, and better social realization. PT Pertamina Gas Operation Kalimantan Area is an operational unit of PT Pertamina Gas under the auspices of Subholding Gas, PT Pertamina Gas Negara has implemented community empowerment programs, one of which is in Martadinata village, Teluk Pandan District, Kutai Kartanegara Regency. One of the programs that has been successful in Martadinata village is the Marta Tani Mandiri program. Starting from the community's habit of using chemical fertilizers and fuel oil in managing agriculture, PT Pertamina Gas Operation Kalimantan Area tries to change these habits to create green agriculture. The embodiment of green agriculture is that Martadinata village farmers are able to manage agricultural land by prioritizing low environmental impact and are able to contribute to environmental improvement. The implementation of sustainable agriculture using self-sufficient agricultural products and the implementation of new and renewable energy can change habits and engage farmers in sustainable environmental protection. Beyond environmental concerns, the ongoing program has also improved the social and economic quality of life.